How to Teach Chinese Language to Thai Students - Yang, Tiange (Journal of Sinology (วารสารจีนวิทยา), 2013)
This article discusses on “How to teach Chinese language to Thai students”. The author proposes that the purpose of Chinese language teaching is to develop students’ Chinese communication skills. Classroom should have student-based activities in order to encourage students to actively use Chinese in the classroom. Teachers should use Chinese language as a medium to teach the students and to create Chinese language environment. The author also discusses and gives some opinions on “using Pinyin or phonetic symbols, using simplified Chinese characters or traditional Chinese characters, Mandarin Chinese teachers’ pronunciation problems etc.